We need to expand the square binomial and then multiply:
<span>3x(x + 3)^2
= 3x(x + 3)</span>(x + 3<span>)
= 3x(x^2 + 6x + 9)
= 3x^3 + 18x^2 + 27x</span>
Answer: 12.96
Step-by-step explanation:
given data:
Poisson distributio = 3.60
solution:
The Poisson distribution expected value is same as Variance.
which is expressed as = SD^2
therefore;
the expected value
= SD^2
= 3.60^2
= 12.96
Answer:
The answer would be 8.1
Step-by-step explanation:
For the smaller triangle, you use the pythagorean theorem. a squared + b squared = c squared.
To find one of the legs, you do 5 squared - 3 squared = b squared.
25 - 9 = b squared. (BD)
16 = b squared
4 = b
Now for the bigger right triangle. You still use the same tactic.
7 squared + 4 squared = c squared (which is AB)
49 + 16 = c squared
65 = c squared
That means c would equal: square root of 65, which is 8.0622577483 which rounds to 8.1
Answer:
(-38) / (-8)
equals 4.75
a negative divided by a negative is always a positive
Step-by-step explanation: